Траектория движения тела вращения - Шанин, А. А. (ХНУРЕ, 2019)
In the world of sports, body rotation factor is very important. For example, trajectory of a soccer ball from corner to goal; tennis ball twisted by a racket; ping-pong ball in the attacking hits is created by adjustable imposing of two movements: translational and rotational. Modern sports equipment and machines for feeding and rolling balls signif-icantly increase efficiency of using time and effort required to achieve mastery. But very few athletes imagine physics of motion of the "cutting" ball, and even more so laws and equations of motion. Therefore, introduction of computer mathematical modeling is a new step in the development of sports.